PENYELIDIKAN GEOLISTRIK TAHANAN JENIS UNTUK PENDUGAAN POTENSI AIR TANAH DI KAMPUS LAPANGAN PPSDM GEOMINERBA CIPATAT – PADALARANG - Arif Budiyono; Antonius Alex Harmoko (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2019)
Availability of ground water at the PPSDM Geominerba Cipatat field campus - Padalarang is a problem that must be taken seriously enough and planned in order to improve services in the use of the field campus to support education at PPSDM Geominerba. Based on this, a study of the potential for groundwater availability has been carried out to overcome existing problems. One of the efforts made is to conduct a type of geoelectric resistivity investigation to illustrate the potential of groundwater in the field campus area. Measurement and data retrieval is done by Schlumberger (Vertical Electrical Sounding) and dipole-dipole (Profiling) configurations on 5 sounding points and 2 profiling lines. From the investigation conducted, it was found that the area lithology of the field campus was dominated by limestone, with the results of the interpretation obtained 3 main layers, namely: tuff, sand, clay tuff, and limestone. The lower limit of the limestone layer cannot be ascertained through this investigation due to the inadequate length of coverage factor both for sounding techniques and profiling techniques The location around the expected point of GL-3 is a more realistic place for groundwater extraction with a slight shift to the north. The thickness of the low resistivity layer that is not too thick is expected to provide enough contact area to allow storing and capturing more meteoric water besides the surface water collected in the porous layer.